EGDI Impact on Control Corruption in Africa: Exploring E-Government Development Index - Nambassa, Gloria; Nurmandi, Achmad (Policy & Governance Review, 2024)
This study explores the E-Government Development Index (EGDI) and its role in combating corruption in Africa. The main aim is to analyze how EGDI impacts corruption control strategies across African nations. This research is academically and practically important as it examines the intersection of e-government and corruption mitigation, providing valuable insights for policymakers and stakeholders. Using a systematic analysis of Scopus articles, the study reveals that advancements in e-government, measured by EGDI, enhance transparency and efficiency in public administration. The findings indicate that a well-implemented e-government infrastructure, reflected in a higher EGDI, positively influences anti-corruption efforts and governance practices across diverse African contexts. The study concludes that EGDI is crucial in shaping governance frameworks and fostering accountability. This research fills gaps in the literature by illuminating the nuanced relationship between EGDI metrics and corruption mitigation. The findings provide actionable insights for policymakers and stakeholders engaged in governance and development initiatives, highlighting the role of e-government in promoting sustainable development across Africa.